1980
DOI: 10.1007/bf02273089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different soil types on plant growth, leaf pigments and sennoside content in Cassia species

Abstract: Cassia angustifolia (Tinnevelly senna) and C. acutifolia (Alexandrian senna) have great medicinal importance because of their sennoside content in leaves and pods, which are used as purgatives. Such properties have not been observed in C. occidentalis. The maximum growth of these Cassia species was observed in black soil followed by sandy and humus soils. The leaf pigments also increased in black soil. The sennoside content of senna was maximum in sandy soil as compared to other soils. (Pharm. Weekblad Sci. Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The reduction in chlorophyll content may create disturbance in photosynthesis and carbohydrate production, which may lead to less plant growth and oil yield, which is in complete agreement with observed reduction in the oil yield of peppermint due to disturbance in photosynthesis that occurred under stress conditions [34]. Sharma et al [35] observed the maximum growth of cassia species in black soil followed by sandy and humus soils; the leaf pigments were also observed more in black soil than those in other soils. The chlorophyll content of wheat and soybean seedlings in different soil types was different [36,37].…”
Section: Discussionsupporting
confidence: 76%
“…The reduction in chlorophyll content may create disturbance in photosynthesis and carbohydrate production, which may lead to less plant growth and oil yield, which is in complete agreement with observed reduction in the oil yield of peppermint due to disturbance in photosynthesis that occurred under stress conditions [34]. Sharma et al [35] observed the maximum growth of cassia species in black soil followed by sandy and humus soils; the leaf pigments were also observed more in black soil than those in other soils. The chlorophyll content of wheat and soybean seedlings in different soil types was different [36,37].…”
Section: Discussionsupporting
confidence: 76%
“…Secondary metabolite production is also influenced by different soils. For example, a study shows that the sennoside content altered among the sandy soil and black soil grown plants, the sandy soil was reported to have higher sennoside content than black soil 45 .…”
Section: Fig 6: Comparison Of Acetylcholinesterase Inhibitory Activimentioning
confidence: 99%
“…Therefore, phenotypes or plant responses detected using hydroponic systems may vary in magnitude when plants are grown in alternative systems (e.g., soil or agar-based media). These considerations are not unique for hydroponic systems; differential responses can also be observed if plants are grown in different types of soil 11,12 .…”
Section: Disadvantages Of Hydroponic Systemsmentioning
confidence: 99%